Climatological study for understanding the aerosol radiative effects at southwest Atlantic coast of Europe. (15th May 2019) - Sorribas, M.; Andrews, E.; Ogren, J.A.; del Águila, A.; Fraile, R.; Sheridan, P.; Yela, M.
Abstract: In order to describe the means, variability and trends of the aerosol radiative effects on the southwest Atlantic coast of Europe, 11 years of aerosol light scattering (σsp ) and 4 years of aerosol light absorption (σap ) are analyzed. A 2006–2016 trend analysis of σsp for D < 10 μm indicates statistically significant trends for March, May–June and September–November, with a decreasing trend ranging from −1.5 to −2.8 Mm −1 /year. In the 2009–2016 period, the decreasing trend is only observed for the months of June and September. For scattering Ångström exponent (SAE) there is an increasing trend during June with a rate of 0.059/year and a decreasing trend during October with −0.060/year. The trends observed may be caused by a reduction of Saharan dust aerosol or a drop in particle loading in anthropogenic influenced air masses. The relationship between SAE and absorption Ångström exponent is used to assess the aerosol typing. Based on this typing, the sub-micron particles are dominated by black carbon, mixed black and brown carbon or marine with anthropogenic influences, while the super-micrometer particles are desert dust and sea spray aerosol. The mean and standard deviation of the dry aerosol direct radiative effect at the top of the atmosphere (DRETOA ) are −4.7 ± 4.2 W m −2 . DRETOA for marine aerosol shows all observations more negative than −4 W m −2 and for anthropogenic aerosol type, DRETOA ranges from −5.0 to −13.0 W m −2 . DRETOA of regional marine aerosol ranges from −3 to −7 W m −2, as it consists of a mixture of sea salt and anthropogenic aerosol. The variability in DRETOA is mainly dependent on AOD, given that variations in backscatter fraction and the single scattering albedo tend to counteract each other in the radiative forcing efficiency equation. The results shown here may help in interpretation of satellite retrieval products and provide context for model evaluation. Highlights: Trend analyses detect aerosol changes from 2006 to 2016 in southwestern Europe. It is proposed that the trends may be related to specific climatic changes. There is a cooling aerosol direct radiative effect (DRETOA is −4.7 ± 4.2 W m −2 ). DRETOA depends mainly on AOD as b and SSA counteract each other in forcing equation.